The vicious cycle of frailty and pain: a two-sided causal relationship revealed - Zhong, Ruipeng; Chen, Yijian; Zhong, Lanhua; Huang, Guiming; Liang, Weidong; Zou, Yun (Frontiers in Medicine, 2024)
The decline in physiological functions in the older people is frequently accompanied with pain and frailty, yet the causal connection between frailty and pain remains uncertain. In this study, we utilised a two-sample Mendelian randomisation (MR) approach to investigate the potential causal association between frailty and pain.Method: Two-sample bidirectional MR was conducted using summary data from genome-wide association studies to examine the potential causal relationship between frailty (defined by the frailty index and frailty phenotype) and pain. Summary genomewide association statistics were extracted from populations of European ancestry.We also investigated the causal relationship between frailty and site-specific pain, including joint pain, limb pain, thoracic spine pain and low back pain. Causal effects were estimated using the inverse variance weighting method. Sensitivity analyses were performed to validate the robustness of the results.Results: Genetic predisposition to frailty was associated with an increased risk of pain (frailty phenotype odds ratio [OR]: 1.73; P = 3.54×10 -6 , frailty index OR: 1.36; P = 2.43×10 -4 ). Meanwhile, individuals with a genetic inclination towards pain had a higher risk of developing frailty. Regarding site-specific pain, genetic prediction of the frailty phenotype increased the occurrence risk of joint pain, limb pain and low back pain. Reverse MR analysis further showed that limb pain and low back pain were associated with an increased risk of frailty occurrence.This study presented evidence supporting a bidirectional causal relationship between frailty and pain. We highlighted the significance of addressing pain to prevent frailty and recommend the inclusion of pain assessment in the evaluation system for frailty.